Transformation of cashless payments in the European payment card market - Arabadzhy, Kyrylo; Zharnikova, Valeriia; Sobolieva-Tereshchenko, Olena (Management and Entrepreneurship: Trends of Development, 2021)
The purpose of this study is to examine the current state and perspectives of non-cash payments by using payment cards in Ukraine, Poland, Sweden, Romania and Hungary. The factors of transformation of the term "non-cash payments" into the term "payment system" are considered in the article. Methodology: The theoretical and practical database of the bank cards market is considered as an information base of the research. In the course of the research general, scientific, theoretical and empirical methods were used, among which are the following:  analysis and generalization of literature on the research topic, methods of observation and comparison, structural methods, methods of coordination and formalization, graphical and tabular representation of data. The article presents trends in the development of new types of non-cash money, compares the development of the payment card market on a number of criteria and describes the main directions of modern use of payment cards for non-cash payments in the analyzed countries. The European Central Bank (ECB) data set, information from sites National Bank of Ukraine and Central banks of countries were collected for comparative economic research. The research findings show that changes of bank cards market greatly influence the development of non-cash payment in economy. The research findings show that changes in bank cards market greatly influence the development of non-cash payment in economy. The scientific significance of the work is that in article the issue of the factors of transformation of the non-cash settlement system into a payment system. The practical significance of the results is that in article shows in detail the ways to improve the Ukrainian market of bank cards using the experience of other EU countries. This article offers insights on the best European practice and challenges of on the bank cards market during 2015 - 2019 years.JEL Classification: G15, G21, O12.